Enhancing animation studies in creative technology education through an entrepreneurship approach: the UMK experience - Ab. Aziz Shuaib; Ahamad Tarmizi Azizan (2011)
As a new paradigm in Malaysia and in order to develop the Creative Economy, the government of Malaysia has started a range of initiatives and provided numerous incentives for animation studies. Therefore, under the Ministry of Higher Education of Malaysia, the government has approved the establishment of Universiti Malaysia Kelantan (UMK) in 2006 as the 19th public university in Malaysia. One of the programmes offeredis a Bachelor’s degree in Creative Technology. The uniqueness of animation studies offered at UMK is the combination of practical animation production skills and theoretical knowledge in emerging technologies and heritage elements, using an entrepreneurship approach including a practical training and capability to create new markets. This paper will discuss the experience of the Universiti Malaysia Kelantan in enhancing animation studies in creative technology education through an entrepreneurship approach to contribute to the Creative Industry and Creative Economy development in Malaysia